1992
DOI: 10.1128/mcb.12.8.3653
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative elements regulate a melanocyte-specific promoter.

Abstract: Melanocytes are specialized cells residing in the hair follicles, the eye, and the basal layer of the human epidermis whose primary function is the production of the pigment melanin, giving rise to skin, hair, and eye color. Melanogenesis, a process unique to melanocytes that involves the processing of tyrosine by a number of melanocyte-specific enzymes, including tyrosinase and tyrosinase-related protein 1 (TRP-1), occurs only after differentiation from the melanocyte precursor, the melanoblast. In humans, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 48 publications
3
128
0
Order By: Relevance
“…A rate-limiting step in pigment production is catalyzed by the enzyme tyrosinase, which is transcriptionally regulated via a tissue-restricted cis-acting promoter containing a canonical E-box (Ganss et al, 1994;Bertolotto et al, 1996). Identical E-boxes are also found in the promoters of the two other key pigment enzymes tyrosinase-related protein 1 (Tyrp1) and dopachrome tautomerase (Dct), suggesting a conserved mode of transcriptional regulation (Lowings et al, 1992;Yokoyama et al, 1994;Yasumoto et al, 1997;Bertolotto et al, 1998b). In vitro experiments have shown that these conserved sequences are bound and potently transactivated by the tissue-restricted transcription factor MITF.…”
Section: Mitf As a Key Transcription Factor In The Pigment Biosynthesmentioning
confidence: 99%
“…A rate-limiting step in pigment production is catalyzed by the enzyme tyrosinase, which is transcriptionally regulated via a tissue-restricted cis-acting promoter containing a canonical E-box (Ganss et al, 1994;Bertolotto et al, 1996). Identical E-boxes are also found in the promoters of the two other key pigment enzymes tyrosinase-related protein 1 (Tyrp1) and dopachrome tautomerase (Dct), suggesting a conserved mode of transcriptional regulation (Lowings et al, 1992;Yokoyama et al, 1994;Yasumoto et al, 1997;Bertolotto et al, 1998b). In vitro experiments have shown that these conserved sequences are bound and potently transactivated by the tissue-restricted transcription factor MITF.…”
Section: Mitf As a Key Transcription Factor In The Pigment Biosynthesmentioning
confidence: 99%
“…In the melanocyte-specific Tyrosinase Tyrp-1 and Dct2 promoters, the specific E-box elements that are essential for their expression have been shown to bind both the bHLH-LZ transcription factors USF1 and Mitf (4,6,7,26,35,36). To determine whether USF1 could recognize the E box present in the Tbx2 promoter, we performed a DNA binding band shift assay using a radiolabeled oligonucleotide probe spanning the E box and in vitro transcribed/translated (ITT) USF1.…”
Section: Tbx2 Expression In Melanoma Cellmentioning
confidence: 99%
“…Mitf has been shown previously to regulate a number of genes, including Tyrosinase, Tyrp-1, and Dct involved in the manufacture of the pigment melanin, a process specific to melanocytes and the retinal pigment epithelium. The sequences recognized in all these Mitf target promoters are E boxes with the sequence CATGTG, including the highly conserved M-box motif (35).…”
Section: Characterization Of the Tbx2mentioning
confidence: 99%
“…It also plays a crucial role in the control of the tissue-speci®c expression of the melanogenic genes (Ganss et al, 1994;Lowings et al, 1992;Yavuzer et al, 1995). Further, in a previous study, we have shown that microphthalmia, through the binding to the M-box upstream from the TATA box, mediates the e ect of cAMP on the tyrosinase promoter (Bertolotto et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are restricted to melanocytes suggesting the existence of a tissue-speci®c regulatory mechanism which controls the transcription of their genes. A regulatory element, thought to be involved in the cell speci®c expression of the melanogenic enzymes, is conserved in the promoter of the three enzymes (Ganss et al, 1994;Lowings et al, 1992;Yokoyama et al, 1994a). This element, called M-box, binds microphthalmia a transcription factor of the basic-helix ± loop ± helix-leucine-zipper family (b-HLH-LZ) which strongly transactivates tyrosinase and TRP1 promoter activities (Ganss et al, 1994;Lowings et al, 1992;Yavuzer et al, 1995).…”
Section: Introductionmentioning
confidence: 99%